Against polarization. (July 2022) - Davenport, Christian
This extension of Christian Davenport's virtual Presidential address to the Peace Science Society International attempts to: (1) identify as well as confront some of the issues that divide the Peace Science community and (2) provide some ideas/actions about what can be done to fix them. The article is as much a reflection on where we have been as it is a call to where we must go.